Climate Change Impacts on Urban Environmental Systems: A Review-Based Analysis with Emphasis on Sustainable Urban Resilience - Amirsarvari, Shahrzad (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
Climate change intensifies interconnected risks to urban environmental systems, threatening ecological integrity, infrastructure performance, and human well-being. This study examines climate change impacts on urban environmental systems and identifies resilience strategies supporting urban adaptation. A semi-systematic review of peer-reviewed literature from Scopus and Web of Science (2020–2025) was conducted using predefined inclusion criteria and thematic analysis. The findings identify four dominant urban climate risks-heat stress, flooding, air pollution, and water scarcity-affecting critical environmental subsystems including green spaces, water infrastructure, and air quality regulation. three major resilience pathways are highlighted: integrated governance and planning, nature-based solutions, and adaptive infrastructure systems. By synthesizing fragmented research through a socio ecological resilience framework, this study provides a reproducible analytical approach to support evidence-based urban climate adaptation and planning.